Metal particle induced spacer surface charging phenomena in direct current gas-insulated transmission lines. (15th June 2021) - Xing, Yunqi; Sun, Xinbo; Yang, Yang; Mazzanti, Giovanni; Fabiani, Davide; He, Jinliang; Li, Chuanyang
Abstract: The interpretation of the surface charge pattern of spacers in gas-insulated transmission lines (GIL) is a research topic with great importance, which requires a comprehensive understanding of charge behaviors at physical interfaces. Here, we report a surface charging phenomenon of spacers in the presence of metal particles inside the direct current (DC) GIL. The charging of spherical metal particles on the spacer surface appears as dotted discontinuously distributed charge spots, which are due to the charge injection from the induced charge of the metal particle and gas ionization over the metal particle surface. Concentrically distributed bipolar charge patterns are seen to build up, which are due to the surface trapping of charges from gas ionization at the end tip of the acicular metal particle. The lateral type of ionization obeys the law of dielectric barrier discharge of the needle-plate electrode in an intense DC electric field, which may bring significant influence on the safety of the spacer. The study in this letter provides direct evidence demonstrating the surface charge patterns of spacers in the presence of metal particles, which serves as an important basis for the design of DC GIL.